1990
DOI: 10.1144/gsl.mem.1990.012.01.21
|View full text |Cite
|
Sign up to set email alerts
|

The Silurian and Early Devonian biogeography of ostracodes in North America

Abstract: Silurian and Early Devonian ostracode associations in North America represent at least three ecotypes, a leperditicopid association, a large beyrichiacean association, a mixed association, and possibly a fourth, spinose podocopid association, or Thuringian ecotype. Comparison of the large beyrichiacean association and mixed association ecotypes indicates the presence of three informal ostracode provinces, the Appohimchi, Baltic-British and Cordilleran, which remained relatively constant in geographical positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…The genus was never formally described, but Berdan noted it most closely resembled forms assigned to the genus Carinokloedenia from Lochkovian age deposits of northern France and Pragian age deposits of Podolia in southwestern Ukraine (Berdan 1971(Berdan , 1990Brookins et al 1973). 1977) also observed that the undescribed Eastport ostracode (cf.…”
Section: Ostracode Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The genus was never formally described, but Berdan noted it most closely resembled forms assigned to the genus Carinokloedenia from Lochkovian age deposits of northern France and Pragian age deposits of Podolia in southwestern Ukraine (Berdan 1971(Berdan , 1990Brookins et al 1973). 1977) also observed that the undescribed Eastport ostracode (cf.…”
Section: Ostracode Datamentioning
confidence: 99%
“…Carinokloedenia) bore affi nities to those in Podolia, although he too noted they represented a new genus. Based on the close resemblance of the Eastport forms to the Devonian age European material, both paleontologists felt justifi ed in assigning an Early Devonian age to the Maine unit (Martinsson , 1977Berdan 1971Berdan , 1990Brookins et al 1973). However, biostratigraphic correlations based on new and undescribed genera are hardly robust, no matter how closely allied to other described genera.…”
Section: Ostracode Datamentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast these Avalonian-Baltic-Laurentian faunas had by this time become markedly different from the Gondwanan shelly faunas, indicating that a widening Rheic Ocean had developed between Avalonia and Gondwana (Cocks & Fortey, 1982). However, although most of the Silurian ostracod faunas of Avalonia and Baltica became the same, they were substantially different from those in Laurentia up to latest Silurian times (Berdan, 1990), indicating that, although brachiopod and trilobite spat were able to cross the narrowing Iapetus Ocean, it was a seaway still deep enough to act as an effective barrier to young ostracods, which did not go through a pelagic stage. In contrast, by early middle Devonian times, the faunal evidence indicates that Avalonia was inseparable from Baltica and Laurentia and merely represented the seaboard margin of the large palaeocontinent of Laurussia.…”
Section: Faunal Changes With Timementioning
confidence: 89%
“…By the latest Caradoc, many brachiopod and trilobite species had been able to cross the ocean, so that, in Silurian times, faunal distinctions across Iapetus can only be made using less mobile animal groups: non-marine fish did not cross Iapetus until the Ludlow (Turner & Turner, 1974;Young, 1990), while benthic ostracodes were distinct until Emsian times (Berdan, 1990). Thus palaeontolological indicators of the suture between Avalonia and Laurentia are much more evident in the earlier Palaeozoic, but a few indicators persist in certain shallow water and non-marine environments until early Devonian times.…”
Section: B the Northern Marginmentioning
confidence: 99%